Comparison of accuracy of CT parameters across chest, low-dose lung, and abdominal CT in diagnosing steatotic liver disease - Yan Li; Jiahao Wang; Gengyu Xu; Yixin Si; Kaiyao Huang; Yinquan Ye; Yun Peng; Yuanyuan Liu (BMC Medical Imaging)
Abstract Objective This study aims to determine the accuracy of computed tomography (CT) parameters obtained from three various scanning protocols (chest CT, low-dose lung CT, and abdominal CT) in diagnosing steatotic liver disease (SLD). Materials and methods This retrospective study included 234 individuals who underwent chest CT, low-dose lung CT, or abdominal CT. SLD presence or absence was confirmed through ultrasound in all participants. Two radiologists independently measured the CT attenuation values of the liver (CTL) and spleen (CTS). The differences (CTL−S) and ratios (CTL/S) between liver and spleens values were calculated. Independent sample t-tests or Mann–Whitney U tests were used to compare CTS, CTL, CTL−S, and CTL/S between SLD and control groups. One-way analysis of covariance or Kruskal–Wallis H tests were conducted to compare the parameters across scanning protocols. Receiver operating characteristic (ROC) analysis was performed. Results The parameters (CTL, CTL−S, and CTL/S) were significantly lower in the SLD group than in the control group across all scanning protocols (P < 0.001). In the control group, significant differences in CTS and CTL were observed among the three scanning protocols (P < 0.05), while non-statistically significant differences were found for CTL−S or CTL/S across protocols in either group (P > 0.05). The ROC analysis revealed abdominal CTL as the most accurate diagnostic marker for SLD (area under the curve [AUC]: 0.894, sensitivity: 90.91%, specificity: 83.33%). CTL−S maintained stable diagnostic performance across protocols (AUC range: 0.813–0.816). The low-dose protocol achieved the best performance for CTL/S (AUC: 0.810), demonstrating high specificity (94.34%) despite moderate sensitivity (64.81%). Conclusion Both chest CT and low-dose CT-derived parameters demonstrated diagnostic accuracy comparable to that of abdominal CT in assessing SLD, suggesting their potential as viable alternatives in specific clinical scenarios.